2011
DOI: 10.1007/s10562-011-0608-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production by Ethanol Steam Reforming on NiCuMgAl Catalysts Derived from Hydrotalcite-Like Precursors

Abstract: Cu-promoted NiMgAl catalysts derived from hydrotalcites were synthesized by the urea hydrolysis method for ethanol steam reforming. The effect of Cu content on catalytic properties of the NiMgAl catalysts was studied. These catalysts were characterized by X-ray diffraction, thermogravimetric and differential analyses, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy and temperature-programmed reduction. The addition of small amounts of Cu to NiMgAl catalysts leads to the increase of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 46 publications
1
32
0
1
Order By: Relevance
“…This transition is related to the release of interlayer water molecules from the structure. The second DTG-DTA peak occurs at temperatures between 248 and 268°C and is commonly ascribed to the removal of hydroxyl host-layers and CO 3 2-from the structure 34 , although this peak might include the release of NO provided by the decomposition of nitrates from the precursors. Table 1 shows that the second peak is shifted towards higher temperatures for the MgCoAl sample, which suggests a higher thermal stability for this material 35 .…”
Section: Resultsmentioning
confidence: 99%
“…This transition is related to the release of interlayer water molecules from the structure. The second DTG-DTA peak occurs at temperatures between 248 and 268°C and is commonly ascribed to the removal of hydroxyl host-layers and CO 3 2-from the structure 34 , although this peak might include the release of NO provided by the decomposition of nitrates from the precursors. Table 1 shows that the second peak is shifted towards higher temperatures for the MgCoAl sample, which suggests a higher thermal stability for this material 35 .…”
Section: Resultsmentioning
confidence: 99%
“…[58][59][60][61][62][63][64] Additionally, by introducing two different reducible cations in the LDH structure (e.g. Ni-Cu; [65][66][67] Ni-Co, [68][69][70] Pd-Cu, 71,72 among others), the subsequent thermal activation/ reduction can lead to the formation of bimetallic catalysts, whose catalytic and stability properties are generally better than those of the respective monometallic systems. The anion-exchange capacity of LDHs has also been exploited as a way to incorporate well-dispersed catalytic species in the interlayer-gallery space.…”
Section: Metal-supported Catalystsmentioning
confidence: 99%
“…The addition of appropriate metals to Ni-based catalysts can often bring about high reforming activity and selectivity to hydrogen. As is found that the addition of Cu to Ni-based catalysts is beneficial to water-gas-shift reaction and dehydrogenation, thus enhances the hydrogen production [84,85]. Lanthanide metals can promote the ease of catalyst reduction and decrease the reduction temperature [86,87].…”
Section: Promoter Effectmentioning
confidence: 99%